Asymmetries in Peer Interaction: The Effect of Social Representations of Gender and Knowledge Asymmetry on Children's Cognitive Development. - Zapiti, Anna; Psaltis, Charis (My University, 2012)
This study examines the role of social representations of gender and knowledge as sources of asymmetry on the features of children's interactions as well as on their cognitive development. The research was carried through an innovative pre-test, first interaction, second interaction, post-test design. One hundred fifty-nine children of the same age (6.5-7.5 years old) but of different levels of knowledge of a spatial-transformation task collaborated in same-sex and opposite-sex dyads to find a joint solution. In the first interaction, a child less developmentally advanced (NC) had to work with a child more developmentally advanced (TC), whereas in the second interaction of the same gender composition, the same NC had to work with a fresh NC. Cognitive progress was assessed using pre-test to post-test gains. The results revealed that the gender composition of the pairs and knowledge asymmetry influence not only the behavioral patterns and strategies that each partner employs in the interaction but also the cognitive outcomes of the children. These findings shed more light to the process through which socio-cognitive conflict gets resolved, which was considered until now a "black box".
Keywords: Child development; Knowledge; Gender, education & development series